ANALYZING THE PARAMETERS AFFECTING THE QUALITY OF REFUSE DERIVED FUEL PELLETS DERIVED FROM MUNICIPAL SOLID WASTE - MUAYAD, MARYAM; ABBAS, QABAS; ABDULKADER, ZAHRAA (Journal of Duhok University, 2020)
One of the major factors that play a role in threatening our climate maintenance is the non-ecofriendly energy production and finding an alternative to this is essential. Refuse-derived fuel (RDF) is an alternative process for non-ecofriendly energy production in which fuel is produced from various types of local waste, including municipal solid waste (MSW). It diverts the landfill waste into a source of energy supplier. This review paper examines the parameters that affect the quality of the Refuse-derived fuel (RDF) that is derived from municipal solid waste (MSW) by reviewing prior studies from multiple sources; experiment-based research papers. The examined parameters from the collected data which included the moisture content, the ash content, Calorific value, Sulfur content, Chlorine content, Carbon content, as well as the content of heavy metals; Cadmium (Cd), Chromium (Cr), Nickel (Ni), Silver (Ag), Zinc (Zn), Lead (Pb), Copper (Cu), and Arsenic (As) were descriptively analyzed in comparison to the typical contents found in the Refuse-derived fuel (RDF) as these typical contents determine the quality of these pellets for producing energy. Some of the collected data for some parameters fell within their typical range. Yet, some did not.